Evaluación de la Viabilidad y Calidad de la Semilla de Maíz (zea mays, l), tras diferentes métodos de Secado en Salache –Latacunga –Cotopaxi 2017. - Pila Cando, Daysi Amparo (2017)
The present investigative work is based on the evaluation of the viability and quality of drying corn seeds through by the appliance of microwave oven technology, microwave oven with temperature and conventional controller again sun drying. The main objectives were: obtain the inflecting seeds drying applying four methods, evaluate its energy efficiency, analyze the viability, and field survive. So were obtained corn seeds after that was carried out drying with different methods, in the microwave oven three different powers were evaluated, 70, 140 and 210 W, in this one were evaluated temperatures: 35, 55 and 75 ° C and in the conventional one 55 ° C. Results were obtained the inflecting seeds drying for each temperature determining its humidity 12% in a power of 70W, it was necessary 60 minutes, the power 140W 13m. and in a power of 210W 10m., for the microwave oven with A temperature controlled at 35 ° C, 1 hour and 30min, for 55 ° C 1 hour with 15 min, 75 ° C 35m. And for the conventional oven at 55 ° C it is taken 16 hours, for drying in the sun 19 days and 12 hours, proving that the technology of the (ovens) reduces the time of corn seeds drying. Afterwards, was evaluated the viability of the seeds. For this, germination tests were carried out, which consisted of the culture of the seeds in Petri dishes on a filter paper moistened with distilled water, the emergence of the radicle was observed, which determined the success of Germination, the results final of germination for the HW (microwave oven) were 45% for power of 70W, 5.71% for power 140 and 0% for 210 W, for oven with temperature controller 90% At 35 ° C, 81.25% at 55 ° C, 12% at 75 ° C, for the conventional oven 99.28% at a temperature of 55 ° C and for the control 97.14%, field survival was evaluated by a randomized block design (DBCA), recorded the number of surviving plants and the height of plants per month of planting. Seeds dried in the oven at a temperature of 55 ° C showed the best results, with an average survival of 100% and a plant height of 11.61cm per month. The results has been evidencing microwave drying technology decreases drying times and increases energy efficiency, but the effect of power decreases the viability of the seed. When analyzing the data of the oven with controller temperature is observed that the viability is not affected and that this variable depends more on the increase of the temperature than the effect of the microwave oven.